Inhibition of GSK3 Represses the Expression of Retinoic Acid Synthetic Enzyme ALDH1A2 via Wnt/β-Catenin Signaling in WiT49 Cells - Li, Yifan; Gong, Hui; Ding, Jiangfeng; Zhao, Fujuan; Du, Jihui; Wan, Jun; Zhang, Juan; Liu, Shaoxiong; Li, Jing; Wang, Lei; Zhou, Bei (Frontiers in Cell and Developmental Biology, 2020)
Organogenesis, including renal development, requires an appropriate retinoic acid concentration, which is established by differential expression of aldehyde dehydrogenase 1 family member A2 (ALDH1A2) and cytochrome P450 family 26 subfamily A/B/C member 1 (CYP26A1/B1/C1). In the fetal kidney, ALDH1A2 expresses in the developing stroma and renal vesicle and its derivatives but does not present in the ureteric bud. It remains unclear what may contribute to this expression pattern. Here we show that the glycogen synthase kinase 3 alpha/beta (GSK3A/B) inhibitor CHIR99021 significantly represses ALDH1A2 expression in WiT49, which is a Wilms’ tumor cell line that exhibits “triphasic” differential potential and is used as a fetal kidney cell model. CHIR99021 fails to suppress ALDH1A2 as β-catenin is inhibited, suggesting that the downregulation of ALDH1A2 by CHIR99021 is through Wnt/β-catenin signaling. Ectopic expression of mouse Wnt1, Wnt3a, Wnt4, and Wnt9b represses ALDH1A2 expression in WiT49 cells. Using immunohistochemistry, we show an inverse correlation of Aldh1a2 expression with β-catenin in rat E18.5 kidney. ChIP demonstrated that β-catenin is recruited to the ALDH1A2 promoter, the conserved intron1G, and another site within intron 1 of ALDH1A2. Using a luciferase assay, we further show that the ALDH1A2 promoter and the intron1G element are involved in the repression of ALDH1A2 expression by CHIR99021. Our work demonstrates that ALDH1A2 expression can be directly repressed by the Wnt/β-catenin signaling in fetal kidney cells, suggesting that Wnt/β-catenin may play a role in maintaining the expression pattern of ALDH1A2 in the fetal kidney, thus controlling the availability and localization of retinoic acid and regulating aspects of kidney development.